Berry flavonoids are differently modulated by timing and intensities of water deficit in Vitis vinifera L. cv. Sangiovese - Palai, Giacomo; Caruso, Giovanni; Gucci, Riccardo; D’Onofrio, Claudio (Frontiers in Plant Science, 2022)
In this work we tested the effect of different regulated deficit irrigation (RDI) regimes on berry flavonoids content and their relative biosynthetic pathways. Vines were subjected to six irrigation regimes over two consecutive years: a) full irrigation during the entire irrigation period (FI); b) severe water deficit during the lag phase (RDI-LS); c) moderate (RDI-1M) or d) severe (RDI-1S) deficit between fruit set and veraison; e) moderate (RDI-2M) or f) severe (RDI-2S) deficit from veraison through harvest. Berries from both RDI-1 treatments showed the highest accumulation of anthocyanins, up-regulating the expression of many genes of the flavonoids pathway since the beginning of veraison until harvest, far after water deficit was released. Although to a lesser degree than RDI-1, both post-veraison water deficit treatments increased anthocyanins concentration, particularly those of the tri-substituted forms, overexpressing the F3’5’H hydroxylases. The moderate deficit irrigation treatments enhanced anthocyanins accumulation with respect to the severe ones either if applied pre- or post-veraison. The water deficit imposed during the lag phase downregulated many genes throughout the flavonoid pathway, showing a slight reduction in the anthocyanins accumulation. The measurements of cluster temperature and light exposure highlighted that under deficit irrigation conditions the effects induced by water stress prevailed over that of light and temperature in regulating anthocyanins biosynthesis. Flavonols concentration was higher in RDI-1S berries, due to the up-regulation of the flavonol synthases and the flavonol-3-O-glycosyltransferases. In this case, the higher cluster light exposure induced by water deficit had a major role in flavonols accumulation. We conclude that the timing and intensity of water stress strongly regulate the berry flavonoids accumulation and that proper management of deficit irrigation can modulate the phenylpropanoid and flavonoid pathways.